PEMANFAATAN SOSIAL MEDIA DALAM MENGOPTIMALKAN PEMASARAN HASIL UMKM MINYAK KELAPA TORA BEKA DI DESA BEKA KABUPATEN SIGI BIROMARU - Moh. Faldi; Mohammad Ega Nugraha; Erwan Sastrawan (LPPM Universitas Bina Bangsa, 2023)
Beka Village is located in Marawola Subdistrict, Sigi Regency on the Palu Banggayang axis road which has abundant natural products including coconut which is quite dominant so that the people of Beka Village take advantage in making Traditional Coconut Oil named Tora Beka Coconut Oil. However, in this method, the Beka Village Community plays a very important role because this research aims to prosper the Tora Beka Coconut Oil MSME players so that MSME business actors can find out the benefits of selling on social media and can maintain their business longer